Characterization of the physicochemical variables of the quality of the water in the Betania reservoir - Carrera, Silvia Cristina
Fish cage culture became economically viable and socially important during the last 15 years in the economy activity Reservoir Betania and has become the second most important economic source, after the electrical power generation. The objective of the present study was to characterize some physicochemical variables of water quality in ten points of the Betania reservoir (Huila- Colombia) between the years 2013-2015. In order to obtain the water samples, a Van Door Bottle was used, and the on-site physicochemical parameters were determined by taking the samples at a depth of 20 cm using a YSI 556 Multiparametric equipment to take the dissolved oxygen readings (mg/L) and the percentage dissolved oxygen saturation, Temperature (°C), pH and its conductivity (μs/cm). The sample of Ammonium (mg/L), Nitrite, Alkalinity and its Hardness were taken with the equipment photometer YSI 9500. The measure of the Transparency of the water was taken with the Sechi disk. All of these analyzes were based on APHA 1998 procedures. Inferential analyzes of two factors, using the general linear model, repeated measures ANOVA and the Kruskal-Wallis test as a non-parametric alternative, p≤0.05. The average values and their respective standard deviations of the physicochemical variables were: Temperature (°C) 26.2 ± 0.5, Dissolved Oxygen (mg/L) 5.9 ± 0.5, Percentage of Dissolved Oxygen 72.7 ± 6.6, pH (Units) 8.0 ± 0.2, Ammonium (mg/L) 0.090 ± 0.021, Nitrite (mg/L) 0.035 ± 0.006, Alkalinity (mg/L) 5 ± 3.6, Hardness (mg/L) 48.7 ± 3.2, Conductivity (µs/cm) 167.4 ± 21.2 and Transparency (cm) 88.3 ± 6.5 physicochemical variables were: Temperature (°C) 26.2 ± 0.5, Dissolved Oxygen (mg/L) 5.9 ± 0.5, Percentage of Dissolved Oxygen 72.7 ± 6.6, pH (Units) 8.0 ± 0.2,